Fabrication of functional ameloblasts from hiPSCs for dental application - Kim, Ka-Hwa; Kim, Eun-Jung; Kim, Hyun-Yi; Li, Shujin; Jung, Han-Sung (Frontiers in Cell and Developmental Biology, 2023)
Tooth formation relies on two types of dental cell populations, namely, the dental epithelium and dental mesenchyme, and the interactions between these cell populations are important during tooth development. Although human-induced pluripotent stem cells (hiPSCs) can differentiate into dental epithelial and mesenchymal cells, organoid research on tooth development has not been established yet. This study focused on the hiPSC-derived human ameloblast organoid (hAO) using a three-dimensional (3D) culture system. hAOs had similar properties to ameloblasts, forming enamel in response to calcium and mineralization by interaction with the dental mesenchyme. hAOs simultaneously had osteogenic and odontogenic differentiation potential. Furthermore, hAOs demonstrated tooth regenerative potential upon interaction with the mouse dental mesenchyme. Our findings provide new insights into a suitable hiPSC-derived dental source and demonstrate that hAOs can be beneficial not only for tooth regeneration but also for the study of various dental diseases for which treatment has not been developed yet.